PARTISIPASI POLITIK MASYARAKAT TERHADAP PEMILIHAN UMUM PERSPEKTIF GOOD GOVERNANCE - asrizal asrizal (Jurnal Bawaslu Provinsi Kepulauan Riau, 2020)
Direct general election have become an inseparable part in the development of democracy and in realizing proper governance. To achieve this, it is necessary to conduct research on how to find out the level of political participation of the community towards a good governance perspective election. This research is a literature study (library research). The data collection technique is done by examining books, texts, archives and documents. The type of implementation is description, with descriptiveanalytical data analysis. The results of this study are in the implementation of elections, the government needs to apply the principles of good governance as a foundation for the formulation and implementation of good state policies. Good governance is important to be implemented in terms of increasing political transparency.This is an effort to improve the quality of public political participation and to avoid irregularities in the conduct of elections. If the election is not managed using the principles of good governance, then most likely the election is used by people who are not responsible.